2020
DOI: 10.1002/ags3.12390
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted minimally invasive esophagectomy for esophageal cancer: Meticulous surgery minimizing postoperative complications

Abstract: Minimally invasive esophagectomy (MIE) has been reported to reduce postoperative complications especially pulmonary complications and have equivalent long‐term survival outcomes as compared to open esophagectomy. Robot‐assisted minimally invasive esophagectomy (RAMIE) using da Vinci surgical system (Intuitive Surgical, Sunnyvale, USA) is rapidly gaining attention because it helps surgeons to perform meticulous surgical procedures. McKeown RAMIE has been preferably performed in East Asia where squamous cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…In this study, robot-sewn anastomosis provided an anastomotic leak rate of 3.3% ( n = 1, ECCG, Type III). This finding is consistent with that reported by other similar studies ranging from 0 to 32% (Table 4 ) and with the average anastomotic insufficiency rate (up to 5.6%) reported by other experiences of Ivor Lewis RAMIE with mechanical intrathoracic anastomosis [ 8 ]. Of note is the fact that the ICAN randomized controlled study (in agreement with other not randomized studies [ 28 30 ]) has recently shown that in the setting of a MI approach, intrathoracic anastomosis is associated with a clinically relevant lower leakage rate compared to cervical anastomosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, robot-sewn anastomosis provided an anastomotic leak rate of 3.3% ( n = 1, ECCG, Type III). This finding is consistent with that reported by other similar studies ranging from 0 to 32% (Table 4 ) and with the average anastomotic insufficiency rate (up to 5.6%) reported by other experiences of Ivor Lewis RAMIE with mechanical intrathoracic anastomosis [ 8 ]. Of note is the fact that the ICAN randomized controlled study (in agreement with other not randomized studies [ 28 30 ]) has recently shown that in the setting of a MI approach, intrathoracic anastomosis is associated with a clinically relevant lower leakage rate compared to cervical anastomosis.…”
Section: Discussionsupporting
confidence: 93%
“…The creation of an intrathoracic anastomosis is considered quite challenging even during MIE owing to the intrinsic limitations of this technique and so far, no general consensus exists on the optimal anastomosis [ 7 ]. Recently, a robotic approach has been implemented to facilitate complex minimally invasive (MI) procedures by combining the optimal advantage of its ergonomics [ 8 ]. This technology might be particularly useful for the thoracic stage of Ivor Lewis en-bloc esophagectomy (ILE), especially when a hand-sewn esophagogastrostomy is planned.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgical systems with full articulation of instruments, tremor ltering, and motion scaling can potentially overcome the procedural di culties in endoscopic surgery [7]. However, we still encounter challenging cases of RAMIE in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the RAMIE has spread rapidly. Robotic surgical systems with full articulation of instruments, tremor ltering, and motion scaling can potentially overcome the procedural di culties in endoscopic surgery [7]. However, we still encounter challenging cases of RAMIE in clinical settings.…”
Section: Introductionmentioning
confidence: 99%